Application of allogeneic adult mesenchymal stem cells in the treatment of venous ulcers: A phase I/II randomized controlled trial protocol - Víctor J. Costela-Ruiz; Encarnación González-Vigil; Olga Espinosa-Ibáñez; Rosario Mata Alcázar – Caballero; Lucía Melguizo-Rodríguez; Olga Fernández-López; Salvador Arias-Santiago (PLoS ONE, 2025)
Objective To evaluate the feasibility, safety and efficacy of the cutaneous application of Bioengineered Artificial Mesenchymal Sheet (BAMS) in venous leg ulcers (VLUs) versus conventional treatment. Methods This protocol is based on the design of a Phase I/II, multicenter, randomized, controlled, open-label clinical trial investigating the application of a biological dressing supplemented with mesenchymal stem cells (NCT05962931). The clinical trial is being conducted in 2 primary care units within the Granada Metropolitan Health District. A total of 20 patients with VLUs are being randomized (1:1) into 2 intervention arms: a control group and a treatment group. The intervention in the treatment group consists of the local application of 4 doses of BAMS, administered once per week, while the control group receives conventional therapy. Feasibility will be assessed based on the ability to complete the administration of 4 doses in at least 80% of the patients in the treatment group. Safety will be evaluated by analyzing the incidence of adverse effects and serious adverse effects. Efficacy will be assessed in terms of the percentage of wound closure (measured by wound area reduction), macroscopic assessment of the lesion (visual macroscopic analysis and RESVECH 2.0 scale), analysis of growth factors and inflammatory cytokines (ELISA test), pain levels (VAS scale) and quality of life (CIVIQ 20). Results If confirmed, BAMS-based therapy may provide an effective treatment for VLUs, potentially reducing wound closure time and associated complications. This therapy could significantly enhance patients’ quality of life due to the regenerative and analgesic properties of the biological dressing. Discussion Given the biological activity of mesenchymal stem cells, an accelerated healing effect is expected in the treatment group. This could lead to shorter healing times for chronic wounds, resulting in significant benefits for patients, healthcare professionals, and overall healthcare costs. Trial registration NCT05962931.